Ru-based catalyst for high-current-density water electrolysis hydrogen production and preparation method of Ru-based catalyst
By loading Ru doped Co3S4 catalyst on the foam nickel matrix, the problem of the performance of electrolytic hydrogen production catalyst deteriorates under high current density, achieving high efficiency and stability of the catalyst, and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411107309.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-24
AI Technical Summary
The existing electrolytic hydrogen production catalyst has deteriorated catalytic performance under high current density and is complex in preparation process, so it cannot be effectively applied to industrialization.
The foam nickel foam matrix is loaded with Ru doped Co3S4 catalyst, and prepared by ion exchange, changing the electronic structure of Ru, enhancing the Co-S-Ru bond length, inhibiting the excessive oxidation of Ru, and forming a rough surface to promote hydrogen precipitation.
The activity and stability of the catalyst are improved, making it suitable for hydrogen production under high current density, with excellent hydrogen precipitation reaction stability and efficient HER performance.
Smart Images

Figure CN119177465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for producing hydrogen by electrolysis of water, and in particular to a Ru-based catalyst for producing hydrogen by electrolysis of water at a high current density and a preparation method thereof. Background Art
[0002] Water electrolysis hydrogen production technology has the advantages of high energy efficiency, high yield and the ability to produce high-purity green hydrogen, and is very important for the future energy economy. However, the slow reaction kinetics in the cathode hydrogen evolution reaction hinders its commercial promotion. Therefore, catalysts play a vital role in the cathode hydrogen evolution reaction.
[0003] At present, the catalysts for hydrogen production by electrolysis of water are mostly precious metal materials such as Pt, Rh, and Ir, which are expensive. Therefore, cheap platinum group metal ruthenium (Ru) with Pt-like metal activity and abundant d-orbital electrons has good application prospects. However, in actual electrochemistry, as the cathode hydrogen evolution reaction proceeds, metal agglomeration and surface reconstruction occur on the surface of the catalyst, reducing the catalytic performance of the ruthenium catalyst. In the prior art, in order to improve the catalytic performance of ruthenium, it is loaded on a NiMoO4 matrix, but the preparation process of the catalyst is complicated and can only be applied under low current density. Summary of the invention
[0004] In order to prepare a catalyst with high catalytic activity and stability under high current density, the present invention provides a Ru-based catalyst for producing hydrogen by electrolyzing water at high current density and a preparation method thereof.
[0005] In order to achieve the above-mentioned purpose, the specific scheme adopted by the present invention is: a Ru-based catalyst for high current density electrolysis of water to produce hydrogen, including a foamed nickel matrix and an active component loaded on the foamed nickel matrix, and the active component is Ru-doped Co3S4.
[0006] As an optimization scheme for the above-mentioned Ru-based catalyst for electrolysis of water to produce hydrogen at a high current density: the pore size of the foamed nickel matrix is 0.1-10 mm, the porosity is 90-99%, and the pore density is 50-200 PPI.
[0007] A method for preparing a Ru-based catalyst, characterized in that it comprises the following steps:
[0008] S1, dissolving cobalt nitrate, urea and ammonium fluoride in water to obtain a dispersion, and mixing the dispersion with nickel foam (NF) to react to obtain nickel foam-supported Co(OH)2 / NF;
[0009] S2, nickel foam-supported Co(OH)2 / NF and Na2S aqueous solution were mixed to obtain nickel foam-supported Co3S4 / NF;
[0010] S3, immersing the nickel foam-supported Co3S4 / NF nanorods into a RuCl3 aqueous solution for reaction to obtain a nickel foam-supported Ru-Co3S4 catalyst.
[0011] As an optimized solution of the preparation method of the above-mentioned Ru-based catalyst: in S1, the mass ratio of cobalt nitrate, urea and ammonium fluoride in the dispersion is 145.5:120:28.
[0012] As another optimization scheme of the preparation method of the above-mentioned Ru-based catalyst: in S1, the reaction temperature of the dispersion and the nickel foam is 110-130° C., the pressure is 2-3 MPa, and the reaction time is 3-5 h.
[0013] As another optimization scheme for the preparation method of the above-mentioned Ru-based catalyst: in S2, the mass ratio of Na2S in the Na2S aqueous solution to Co(OH)2 / NF supported by nickel foam is 10:1.
[0014] As another optimization scheme for the preparation method of the above-mentioned Ru-based catalyst: in the S2, the concentration of the Na2S aqueous solution is 0.05-0.15 g / ml.
[0015] As another optimization scheme for the preparation method of the above-mentioned Ru-based catalyst: in S2, the reaction temperature of the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution is 100-150°C, the reaction pressure is 2-3MPa, and the reaction time is 5-8h.
[0016] As another optimization scheme of the preparation method of the above-mentioned Ru-based catalyst: in S3, the concentration of the RuCl3 aqueous solution is 0.2-1 mg / ml.
[0017] As another optimization scheme of the preparation method of the above-mentioned Ru-based catalyst: in S3, the reaction temperature is 90-110°C, the reaction pressure is 2-3MPa, and the reaction time is 0.5-3h.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention provides a Ru-based catalyst for hydrogen production by electrolysis of water at a high current density and a preparation method thereof. A nickel foam-supported Ru-Co3S4 catalyst is prepared by ion exchange, that is, Ru atoms are doped into Co3S4 nanorods, and the electronic structure of Ru is changed by means of charge transfer between Ru and Co3S4, thereby improving the activity of the Ru catalyst; at the same time, the bond length of Co-S-Ru is enhanced, and the excessive oxidation of Ru is suppressed, so that it has excellent hydrogen evolution reaction (HER) stability in an alkaline medium.
[0020] 2. In the present invention, the Co3S4 / NF loaded with nickel foam is immersed in a RuCl3 aqueous solution, and Ru is doped into the Co3S4, causing the lattice of Co3S4 to become larger, thereby causing the Ru-Co3S4 catalyst to form a rough surface, promoting the rapid overflow of H2 from the catalyst surface, so that the catalyst can be used for hydrogen production by electrolysis of water at a high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the X-ray diffraction (PXRD) patterns of the products obtained in Example 4 and Comparative Example 1;
[0022] Figure 2 is a transmission electron microscope image of the product obtained in Example 4;
[0023] Figure 3 is a high-resolution transmission electron microscopy image of the product obtained in Example 4;
[0024] Figure 4 is a high-resolution Co 2p orbital XPS graph of the products obtained in Example 4 and Comparative Example 1;
[0025] Figure 5 is the nitrogen isothermal adsorption-desorption curve of the product obtained in Example 4;
[0026] Figure 6 is the nitrogen isothermal adsorption-desorption curve of the product obtained in Comparative Example 1;
[0027] Figure 7 HER polarization curves of the products obtained in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0028] Figure 8 is a comparison diagram of HER polarization curves of the product obtained in Example 4 before and after the accelerated aging test;
[0029] Fig. 9 is a timing current curve diagram of the product obtained in Example 4 at a fixed voltage;
[0030] Fig.10 This is the full water splitting polarization curve diagram after the product obtained in Example 4 is assembled into a Ru-Co3S4 / NF||Ru-Co3S4 / NF electrolyzer;
[0031] Fig.11 This is a timing current curve at a fixed voltage after the product obtained in Example 4 is assembled into a Ru-Co3S4 / NF||Ru-Co3S4 / NF electrolytic cell. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.
[0033] A method for preparing a Ru-based catalyst comprises the following steps:
[0034] S1, dissolving cobalt nitrate, urea and ammonium fluoride in water to obtain a dispersion, wherein the mass ratio of cobalt nitrate, urea and ammonium fluoride in the dispersion is 145.5:120:28. The nickel foam is ultrasonically cleaned in acetone, hydrochloric acid and deionized water to remove the oxide layer on the surface; then, the dispersion and the nickel foam are mixed and reacted to obtain Co(OH)2 / NF loaded on the nickel foam, and the dispersion and the nickel foam are placed in a high-pressure reactor for reaction, and the reaction temperature of the dispersion and the nickel foam is 110-130°C, the pressure is 2-3MPa, and the reaction time is 3-5h.
[0035] S2, nickel foam loaded Co(OH)2 / NF and Na2S aqueous solution are mixed to obtain nickel foam loaded Co3S4 / NF; the mass ratio of Na2S in the Na2S aqueous solution to Co(OH)2 / NF loaded on nickel foam is 10:1, and the concentration of the Na2S aqueous solution is 0.05-0.15 g / ml. The nickel foam loaded Co(OH)2 / NF and the Na2S aqueous solution are placed in a high-pressure reactor for reaction, and the reaction temperature of the nickel foam loaded Co(OH)2 / NF and the Na2S aqueous solution is 100-150°C, the reaction pressure is 2-3 MPa, and the reaction time is 5-8 hours.
[0036] S3, immersing the nickel foam loaded Co3S4 / NF into a RuCl3 aqueous solution for reaction to obtain a nickel foam loaded Ru-Co3S4 catalyst, the concentration of the RuCl3 aqueous solution is 0.2-1 mg / ml, the nickel foam loaded Co3S4 / NF and the RuCl3 aqueous solution are placed in a high-pressure reactor for reaction, and the reaction temperature is 90-110°C, the reaction pressure is 2-3 MPa, and the reaction time is 0.5-3h.
[0037] The nickel foam-supported Ru-Co3S4 catalyst was prepared by ion exchange, that is, Ru atoms were doped into Co3S4 nanorods, and the electronic structure of Ru was changed by charge transfer between Ru and Co3S4, thereby improving the activity of Ru catalyst; at the same time, the bond length of Co-S-Ru was enhanced, thereby enhancing the binding energy between Ru-Co3S4, inhibiting the excessive oxidation of Ru, and making it have excellent HER stability in alkaline medium. The nickel foam-supported Co3S4 / NF was immersed in RuCl3 aqueous solution. The doping of Ru caused the lattice of Co3S4 to become larger, thereby forming a rough surface of the Ru-Co3S4 catalyst, promoting the rapid overflow of H2 from the catalyst surface, so that the catalyst can be used for hydrogen production by electrolysis of water at high current density.
[0038] Example 1
[0039] A Ru-based catalyst for high current density water electrolysis hydrogen production includes a nickel foam substrate and an active component loaded on the nickel foam substrate, wherein the active component is Ru-doped Co3S4, the pore size of the nickel foam substrate is 0.1-10 mm, the porosity is 90-99%, and the pore density is 50-200 PPI. In this embodiment, the pore size of the nickel foam substrate is 5 mm, the porosity is 95%, and the pore density is 100 PPI. The catalyst has good crystallinity, high thermal stability, and a wide and low source of raw material costs; the catalyst has strong repeatability, simple synthesis process equipment, and is suitable for large-scale controllable synthesis and mass production; the catalyst has a rough surface, which promotes the rapid escape of H2 produced by the hydrogen evolution reaction from the catalyst surface, making it suitable for high current density water electrolysis hydrogen production in industry, and has good stability during use.
[0040] Example 2
[0041] A method for preparing a Ru-based catalyst comprises the following steps:
[0042] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 120°C and 2MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0043] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 100°C and 2MPa for 5h to obtain nickel foam-loaded Co3S4 / NF.
[0044] S3, dissolve 15 mg of RuCl3 in 30 ml of water to obtain a RuCl3 aqueous solution, place the nickel foam-loaded Co3S4 / NF and the RuCl3 aqueous solution in a high-pressure reactor, and soak the nickel foam-loaded Co3S4 / NF in the RuCl3 aqueous solution, keep it warm at 90°C and 2 MPa for 0.5 h, wait for the temperature to cool naturally, take it out after drying, and obtain the nickel foam-loaded Ru-Co3S4 catalyst.
[0045] Example 3
[0046] A method for preparing a Ru-based catalyst comprises the following steps:
[0047] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 110°C and 2.5MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0048] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 150°C and 2.5MPa for 8h to obtain nickel foam-loaded Co3S4 / NF.
[0049] S3, dissolve 15 mg of RuCl3 in 30 ml of water to obtain a RuCl3 aqueous solution, place the nickel foam-loaded Co3S4 / NF and the RuCl3 aqueous solution in a high-pressure reactor, and soak the nickel foam-loaded Co3S4 / NF in the RuCl3 aqueous solution, keep it warm at 110°C and 2.5 MPa for 3 hours, wait for the temperature to cool naturally, take it out after drying, and obtain the nickel foam-loaded Ru-Co3S4 catalyst.
[0050] Example 4
[0051] A method for preparing a Ru-based catalyst comprises the following steps:
[0052] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 120°C and 3MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0053] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 120°C and 3MPa for 6h to obtain nickel foam-loaded Co3S4 / NF.
[0054] S3, dissolve 15 mg of RuCl3 in 30 ml of water to obtain a RuCl3 aqueous solution, place the nickel foam-loaded Co3S4 / NF and the RuCl3 aqueous solution in a high-pressure reactor, and soak the nickel foam-loaded Co3S4 / NF in the RuCl3 aqueous solution, keep it warm at 100°C and 3 MPa for 1 hour, wait for the temperature to cool naturally, take it out after drying, and obtain the nickel foam-loaded Ru-Co3S4 catalyst.
[0055] Example 5
[0056] A method for preparing a Ru-based catalyst comprises the following steps:
[0057] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 120°C and 3MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0058] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 120°C and 3MPa for 6h to obtain nickel foam-loaded Co3S4 / NF.
[0059] S3, dissolve 10 mg of RuCl3 in 30 ml of water to obtain a RuCl3 aqueous solution, place the nickel foam-loaded Co3S4 / NF and the RuCl3 aqueous solution in a high-pressure reactor, and soak the nickel foam-loaded Co3S4 / NF in the RuCl3 aqueous solution, keep it warm at 100°C and 3 MPa for 1 hour, wait for the temperature to cool naturally, take it out after drying, and obtain the nickel foam-loaded Ru-Co3S4 catalyst.
[0060] Example 6
[0061] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 120°C and 3MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0062] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 120°C and 3MPa for 6h to obtain nickel foam-loaded Co3S4 / NF.
[0063] S3, dissolve 20 mg of RuCl3 in 30 ml of water to obtain a RuCl3 aqueous solution, place the nickel foam-loaded Co3S4 / NF and the RuCl3 aqueous solution in a high-pressure reactor, and soak the nickel foam-loaded Co3S4 / NF in the RuCl3 aqueous solution, keep it warm at 100°C and 3 MPa for 1 hour, wait for the temperature to cool naturally, take it out after drying, and obtain the nickel foam-loaded Ru-Co3S4 catalyst.
[0064] Comparative Example 1
[0065] Preparation of nickel foam-supported Co3S4 / NF comprises the following steps:
[0066] S1, the nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 minutes to remove the surface oxide layer; 2mmol cobalt nitrate, 8mmol urea and 3mmol ammonium fluoride were dissolved in 30mL water, and ultrasonicated for 15min to obtain a dispersion, and the dispersion and the nickel foam were placed in a 50ml high-pressure reactor, and kept warm at 120°C and 3MPa for 3h to react to obtain Co(OH)2 / NF loaded on the nickel foam.
[0067] S2, dissolve 2.5g of Na2S in 30ml of water to obtain a Na2S aqueous solution, place the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution obtained in S1 in a high-pressure reactor, and keep the nickel foam-loaded Co(OH)2 / NF and the Na2S aqueous solution at 120°C and 3MPa for 6h to obtain nickel foam-loaded Co3S4 / NF.
[0068] Comparative Example 2
[0069] Commercialization of 20% platinum-carbon catalyst.
[0070] Comparative Example 3
[0071] Nickel foam was ultrasonically cleaned in acetone, hydrochloric acid and deionized water for 10 min.
[0072] The Bruker D8 Advance instrument (Cu Kα, ), the Ru-Co3S4 catalyst supported by nickel foam obtained in Example 4 and the Co3S4 / NF supported by nickel foam obtained in Comparative Example 1 were subjected to X-ray diffraction (PXRD) test to obtain an X-ray diffraction (PXRD) pattern, as shown in FIG. Figure 1 As shown, in addition to the Ni peak, there are four peaks at 31.5°, 38.1°, 50.5° and 55.1°, which are the four crystal planes of Co3S4 (311), (400), (511) and (440) (Co3S4 PDF#19-0367). 3+ After ion exchange, Ru-Co3S4 did not generate new peaks. In particular, the diffraction peaks of Ru-Co3S4 had a slight low-angle shift compared with Co3S4, confirming the doping of Ru into Co3S4.
[0073] The nickel foam supported Ru-Co3S4 catalyst obtained in Example 4 was analyzed by transmission electron microscopy. Figure 2 and Figure 3 As shown, Figure 2 Transmission electron microscopy images. Figure 3 This is a high-resolution transmission electron microscope image. Figure 2 It can be seen that the Ru-Co3S4 catalyst supported by nickel foam has a nanorod structure with a rough surface. The diameter of the nanorod is about 140nm. Figure 3 It can be seen that the lattice fringe spacing is 0.283nm, corresponding to the (311) plane of the Co3S4 phase, which is consistent with the XRD analysis results.
[0074] XPS test analysis was performed on the nickel foam supported Ru-Co3S4 catalyst obtained in Example 4 and the nickel foam supported Co3S4 / NF obtained in Comparative Example 1. Figure 4 As shown in Figure 2, in Co3S4, the Co 2p spectrum can be divided into two pairs of peaks, Co 2p3 / 2 and Co2p1 / 2, accompanied by two satellite peaks. The two peaks at 778.3 and 793.5 eV belong to Co 3+ The two peaks at 781.1 and 797.1 eV belong to Co 2+ After Ru doping, the peak of Co moves to the direction with higher binding energy due to the electron transfer from Co to Ru, indicating that Ru is successfully doped into Ru-Co3S4. 3+ / Co 2+The ratio of increases, which is beneficial to the improvement of catalyst activity.
[0075] The Ru-Co3S4 catalyst supported by nickel foam obtained in Example 4 and the Co3S4 / NF supported by nickel foam obtained in Comparative Example 1 were subjected to N2 adsorption-desorption curve tests to obtain N2 adsorption-desorption curves, as shown in FIG. Figure 5 and Figure 6 As shown. Figure 5 and Figure 6 It can be seen that the specific surface areas of Co3S4 and Ru-Co3S4 are 8.14 m 2 g -1 and 11.71 m 2 g -1 Compared with Co3S4, Ru-Co3S4 has a larger surface area, which can expose a large number of electrochemically active sites, which is beneficial to the diffusion rate of protons in the electrolyte and facilitates the desorption of H2 generated at high current density.
[0076] The electrochemical performance of the products obtained in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 was tested on CHI660E. The results are as follows: Figure 7 As shown in the figure, in alkaline solution, the trend of catalytic activity is Ru-Co3S4 / NF>Pt / C / NF>Co3S4 / NF>Ni foam (NF). Among them, the catalytic activity of Ru-Co3S4 catalyst is better than that of commercial Pt / C catalyst. It is worth noting that the current density reaches 10 and 100 mA cm -2 , the overpotential of Ru-Co3S4 / NF is 20 and 141 mV, which is much better than Co3S4 (79 and 249 mV), Pt / C (36 and 212 mV) and NF (169 and 494 mV). 2 , with an overpotential of 313 mV, which has the potential to become a catalyst for hydrogen evolution in water electrolysis at high current density. These indicate that the HER activity of Ru-Co3S4 is significantly better than that of Co3S4, indicating that Ru doping improves the HER activity of Co3S4.
[0077] The electrochemical catalytic stability of the product obtained in Example 4 was analyzed. After 3000 cycles of accelerated aging test, the HER polarization curve did not change much. Figure 8 More importantly, during the electrochemical process of up to 50 h, the output current density is 100 mA / cm 2 Keep the surrounding area unchanged for a long time, such as Fig. 9This indicates that the prepared Ru-Co3S4 / NF nanocatalyst has greater catalytic activity and stability in the process of electrolysis of water to produce hydrogen at a high current density, and the working time and working environment can meet the requirements of industrial applications.
[0078] The product obtained in Example 4 was subjected to a complete water decomposition catalytic analysis. Fig.10 As shown in the figure, due to the excellent electrocatalytic activity and stability of Ru-Co3S4 in the HER reaction, Ru-Co3S4 was used as the electrocatalyst at both the anode and cathode to assemble a two-electrode electrolyzer to evaluate its overall water splitting performance. RuCo3S4||Ru-Co3S4 exhibited excellent overall water splitting performance at 10 mA / cm 2 At a current density of 1.5 V, its voltage is 1.47 V, which is better than the currently commercially available Pt / C / NF||IrO2 / NF electrocatalytic activity (1.59 V@10 mA cm -2 ).
[0079] The product obtained in Example 4 was subjected to a complete water stability analysis. Fig.11 As shown, Ru-Co3S4||Ru-Co3S4 is assembled into a complete water splitting electrolyzer, which can be used at 100mAcm -2 The catalyst can maintain stable catalysis for 50 hours under high current density. This proves that the catalyst has excellent electrocatalytic activity and durability, and can be used to electrolyze water to produce hydrogen under high current density.
[0080] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A Ru-based catalyst for high current density water electrolysis to produce hydrogen, characterized in that: The invention comprises a foamed nickel matrix and an active component loaded on the foamed nickel matrix, wherein the active component is Ru-doped Co3S4.
2. A Ru-based catalyst for producing hydrogen by electrolysis of water at a high current density as claimed in claim 1, characterized in that: The pore size of the foamed nickel substrate is 0.1-10 mm, the porosity is 90-99%, and the pore density is 50-200 PPI.
3. A method for preparing a Ru-based catalyst, characterized in that: The following steps are involved: S1, dissolving cobalt nitrate, urea and ammonium fluoride in water to obtain a dispersion, and mixing the dispersion with nickel foam to react to obtain Co(OH)2 / NF supported by nickel foam; S2, nickel foam-supported Co(OH)2 / NF and Na2S aqueous solution were mixed to obtain nickel foam-supported Co3S4 / NF; S3, immersing the nickel foam-supported Co3S4 / NF nanorods into a RuCl3 aqueous solution for reaction to obtain a nickel foam-supported Ru-Co3S4 catalyst.
4. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In S1, the mass ratio of cobalt nitrate, urea and ammonium fluoride in the dispersion is 145.5:120:
28.
5. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In S1, the reaction temperature of the dispersion and the nickel foam is 110-130° C., the pressure is 2-3 MPa, and the reaction time is 3-5 h.
6. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In the S2, the mass ratio of Na2S in the Na2S aqueous solution to Co(OH)2 / NF supported by nickel foam is 10:
1.
7. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In the S2, the concentration of the Na2S aqueous solution is 0.05-0.15 g / ml.
8. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In the S2, the reaction temperature of the nickel foam-supported Co(OH)2 / NF and the Na2S aqueous solution is 100-150°C, the reaction pressure is 2-3MPa, and the reaction time is 5-8h.
9. The method for preparing a Ru-based catalyst according to claim 1, characterized in that: In the S3, the concentration of the RuCl3 aqueous solution is 0.2-1 mg / ml.
10. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In S3, the reaction temperature is 90-110° C., the reaction pressure is 2-3 MPa, and the reaction time is 0.5-3 h.
